2022
DOI: 10.1108/jwl-01-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Reflective thinking, ambiguity tolerance, and knowledge sharing: application of the motivation-opportunity-ability framework

Abstract: Purpose The purpose of this study is to apply the motivation–opportunity–ability (MOA) framework to investigate the relationships between ambiguity tolerance (AT), reflective thinking (RT) and performance in a complex task to predict knowledge-sharing intent. Design/methodology/approach In this study, 190 subjects performed a complex scheduling task in which they were randomly assigned to either participate in RT or not. Findings Results show that factors of the MOA framework positively predicted knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 122 publications
(170 reference statements)
0
3
0
1
Order By: Relevance
“…Our study adds to the literature on empowering leadership, psychological empowerment, LGO and KSB in many folds. First, KS is a complex process and needs further investigation (Endres and Chowdhury, 2022; Islam and Asad, 2021). Past studies have identified the roles of positive and negative leadership styles in enhancing KS in the workplace (Chaudhary et al , 2021; Guo et al , 2021; Offergelt and Venz, 2022); therefore, extending these studies, we focused on empowering leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study adds to the literature on empowering leadership, psychological empowerment, LGO and KSB in many folds. First, KS is a complex process and needs further investigation (Endres and Chowdhury, 2022; Islam and Asad, 2021). Past studies have identified the roles of positive and negative leadership styles in enhancing KS in the workplace (Chaudhary et al , 2021; Guo et al , 2021; Offergelt and Venz, 2022); therefore, extending these studies, we focused on empowering leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the dynamic and competitive environment of the product market has increased organizational interest in amplifying KS trends to achieve organizational effectiveness (Chatterjee et al , 2022). As organizations are not supposed to exploit employees’ knowledge and share it with others without their willingness (Ipe, 2003), therefore, KS is a complicated process (Endres and Chowdhury, 2022) and needs further investigation (McLarnon et al , 2022; Islam and Asad, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Motivasi merupakan faktor pendorong seseorang dalam melakukan berbagai aktivitas, seorang pekerja menjadi rajin, kreatif, atau tidak kreatif dapat di amati dari motivasi yang ada di dalam diri seseorang tersebut, motivasi sangat berperan penting dalam segala kegiatan yang di kerjakan oleh manusia karena dengan adanya motivasi akan mendorong seseorang untuk melakukan sesuatu secara maksimal (Mahmudi Pradayu, 2017;Endres, 2022;Karimi, 2019;Nuttin, 2022;Sorić, 2021;Tomar, 2024). Mengutip dari Sardiman dalam Yunita Rahmah (2019), indikator motivasi belajar dapat diklasifikasikan sebagai berikut: Namun, pada faktanya dalam mengikuti kegiatan Ormawa mahasiswa sering dihadapkan pada kenyataan sulitnya membagi waktu antara kegiatan Ormawa dengan kegiatan perkuliahan, karena dalam megikuti kegiatan Ormawa mahasiswa memiliki kegiatan yang cukup padat bahkan terkadang jadwal kegiatan Ormawa tersebut berbenturan dengan jadwal perkuliahan, sehingga mahasiswa dihadapkan pada pilihan yang sulit antara tetap mengikuti kegiatan Ormawa dan harus rela meninggalkan perkuliahan atau sebaliknya mengikuti kegiatan perkuliahan dan harus rela meninggalkan kegiatan Ormawa.…”
Section: Pendahuluanunclassified
“…Oehlman et al ( 2016 ) stated that e-portfolio supports reflective learning, facilitates the transfer of knowledge, and actively involves students who are not active enough in the course. Endres and Chowdhury ( 2022 ) concluded in the study that the e-portfolio applied to individuals working in production and service organizations positively affects reflective thinking and motivation. Chang et al ( 2018 ) experimentally determined that there were significant improvements in students’ self-regulation in the study with high school sophomores.…”
Section: Literature Reviewmentioning
confidence: 99%